Method for regulating and controlling surface hydrophilicity and hydrophobicity of boron-doped diamond film and improving degradation performance of organic wastewater

By forming a BDD-ZnO heterostructure on the surface of the boron-doped diamond film, the problem of difficulty in effectively removing organic pollutants in organic wastewater in the prior art is solved, and efficient degradation and cleaning treatment of organic wastewater is achieved.

CN119793434AInactive Publication Date: 2025-04-11KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510041335.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove organic pollutants from organic wastewater, and traditional physical and chemical treatment methods and biological treatment technologies have problems of inefficiency.

Method used

A BDD-ZnO composite material composed of boron-doped diamond film and zinc oxide nanorod array is used to form a heterostructure through hydrothermal reaction, washing, drying and sintering, which regulates the hydrophilicity of the membrane surface and improves the degradation performance of organic wastewater.

Benefits of technology

It has achieved efficient degradation of organic wastewater, and has the characteristics of cleanliness, high stability and high degradation efficiency, and can degrade organic pollutants without distinction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793434A_ABST
    Figure CN119793434A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sewage treatment, and particularly relates to a method for regulating and controlling the surface hydrophilicity and hydrophobicity of a boron-doped diamond film and improving the degradation performance of organic wastewater. The BDD-ZnO composite material provided by the invention is composed of a boron-doped diamond film (BDD) and a zinc oxide (ZnO) nanorod array grown on the boron-doped diamond film, and the boron-doped diamond film and the zinc oxide nanorod array are of a heterostructure. When being used for organic wastewater degradation, the material is slightly limited and interfered by environmental conditions, can indifferentially degrade organic pollutants, has the characteristics of cleanness and high efficiency, and has excellent stability and degradation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sewage treatment, and more specifically relates to a method for regulating the hydrophilicity and hydrophobicity of the surface of a boron-doped diamond film and improving the degradation performance of organic wastewater. Background Art

[0002] With the rapid development of industrialization and urbanization, environmental pollution issues have become increasingly prominent, and the amount of wastewater discharged has increased year by year, and organic wastewater accounts for 60% of the total wastewater discharge. Organic wastewater refers to wastewater with organic pollutants as the main component, mainly including food industry wastewater, chemical industry wastewater, pharmaceutical industry wastewater, textile / printing and dyeing wastewater, petroleum / chemical wastewater, agricultural wastewater, etc. Among them, the pollution caused by antibiotic organic pollutants discharged from pharmaceutical wastewater to water bodies has attracted widespread attention.

[0003] Organic wastewater is difficult to be effectively removed by traditional physical and chemical treatment methods and biological treatment technologies due to its poor biodegradability and the limitations of existing technologies. Therefore, the development of efficient and environmentally friendly organic pollutant treatment technologies has become an urgent problem in the field of environmental science. Summary of the invention

[0004] The purpose of the present invention is to provide a method for regulating the hydrophilicity and hydrophobicity of the surface of a boron-doped diamond film and improving the degradation performance of organic wastewater, so as to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a BDD-ZnO composite material, which is composed of a boron-doped diamond film (BDD) and a zinc oxide (ZnO) nanorod array grown on the boron-doped diamond film, wherein the boron-doped diamond film and the zinc oxide nanorod array are in a heterogeneous structure.

[0007] The second technical solution of the present invention is to provide a method for preparing the above-mentioned BDD-ZnO composite material, comprising the following steps:

[0008] The boron-doped diamond film is immersed in a precursor solution, subjected to hydrothermal reaction, washed, dried, and sintered to obtain the BDD-ZnO composite material;

[0009] The precursor solution is a mixed aqueous solution of zinc chloride and sodium carbonate.

[0010] Furthermore, the boron-doped diamond film is prepared by using methane, hydrogen and a boron source as precursor gases on a single crystal silicon substrate using an MPCVD method, wherein the boron source is diborane.

[0011] For safety reasons and to avoid explosion, the boron source is usually introduced by mixing diborane and hydrogen.

[0012] Optionally, the process parameters for preparing boron-doped diamond film by MPCVD method are: substrate temperature 850-900°C, deposition gas pressure 130-150mbar, microwave power 1.5-2.0kW, hydrogen flow rate 1200-1300sccm, methane flow rate 40-50sccm, boron source flow rate 20-30sccm, and reaction time 6-8h.

[0013] Furthermore, the dosage ratio of zinc chloride, sodium carbonate and water in the precursor solution is 1.47-3.47 mmol:9.43 mmol:40-50 mL.

[0014] Furthermore, the dosage ratio of the boron-doped diamond film to the precursor solution is 0.1-0.3 g: 40-50 mL.

[0015] Furthermore, the temperature of the hydrothermal reaction is 130-150° C., and the time is 12 hours.

[0016] The growth of ZnO nanorods is promoted by the temperature and time of the hydrothermal reaction.

[0017] Furthermore, the washing is performed using deionized water and ethanol.

[0018] Furthermore, the drying temperature is 50-70° C. and the drying time is 12 hours.

[0019] Furthermore, the sintering temperature is 500-600° C. and the sintering time is 1 hour.

[0020] The present invention purifies and optimizes the structure of the material through washing and high-temperature annealing and sintering treatment. After the hydrothermal reaction, the generated zinc oxide is rinsed with deionized water and anhydrous ethanol to remove the sodium chloride impurities generated during the hydrothermal reaction and maintain the purity of the generated zinc oxide. The purpose of the subsequent high-temperature annealing treatment in a tubular furnace is to make the zinc oxide more evenly and densely arranged on the electrode surface and to make the zinc oxide more firmly present on the electrode surface.

[0021] The third technical solution of the present invention is to provide an application of the above-mentioned BDD-ZnO composite material as an electrode material in the degradation of organic wastewater.

[0022] The fourth technical solution of the present invention is to provide a method for regulating the hydrophilicity and hydrophobicity of the surface of a boron-doped diamond film, the steps comprising:

[0023] Using a mixed aqueous solution of zinc chloride and sodium carbonate as a precursor solution, a ZnO nanorod array is generated on the surface of a boron-doped diamond film through hydrothermal reaction, washing, drying, and sintering to form a BDD-ZnO heterostructure, thereby completing the hydrophilicity and hydrophobicity regulation of the surface of the boron-doped diamond film and obtaining a BDD-ZnO composite material.

[0024] Furthermore, the ratio of zinc chloride, sodium carbonate and water in the mixed aqueous solution of zinc chloride and sodium carbonate is 1.47-3.47 mmol:9.43 mmol:40-50 mL.

[0025] Furthermore, the dosage ratio of the boron-doped diamond film to the precursor solution is 0.1-0.3 g: 40-50 mL.

[0026] Furthermore, the temperature of the hydrothermal reaction is 130-150° C., and the time is 12 hours.

[0027] Furthermore, the washing is performed using deionized water and ethanol.

[0028] Furthermore, the drying temperature is 50-70° C. and the drying time is 12 hours.

[0029] Furthermore, the sintering temperature is 500-600° C. and the sintering time is 1 hour.

[0030] Technical solution 5 of the present invention: Provide a method for improving the organic wastewater degradation performance of a boron-doped diamond film, the steps comprising:

[0031] By forming a BDD-ZnO heterostructure on the surface of the boron-doped diamond film, the organic wastewater degradation performance of the boron-doped diamond film is improved;

[0032] The forming of the BDD-ZnO heterostructure on the surface of the boron-doped diamond film comprises: using a mixed aqueous solution of zinc chloride and sodium carbonate as a precursor solution, generating a ZnO nanorod array on the surface of the boron-doped diamond film by hydrothermal method, washing, drying and sintering to form the BDD-ZnO heterostructure.

[0033] Furthermore, the ratio of zinc chloride, sodium carbonate and water in the mixed aqueous solution of zinc chloride and sodium carbonate is 1.47-3.47 mmol:9.43 mmol:40-50 mL.

[0034] Furthermore, the dosage ratio of the boron-doped diamond film to the precursor solution is 0.1-0.3 g: 40-50 mL.

[0035] Furthermore, the temperature of the hydrothermal reaction is 130-150° C., and the time is 12 hours.

[0036] Furthermore, the washing is performed using deionized water and ethanol.

[0037] Furthermore, the drying temperature is 50-70° C. and the drying time is 12 hours.

[0038] Furthermore, the sintering temperature is 500-600° C. and the sintering time is 1 hour.

[0039] Technical solution 6 of the present invention: Provide a method for degrading organic wastewater, comprising the following steps:

[0040] The BDD-ZnO composite material is used as the anode, the platinum sheet electrode is used as the cathode, the electrode clamp is connected, the current density is adjusted to 0.8-1.0A, and the organic wastewater is degraded under ultraviolet conditions.

[0041] Furthermore, the organic matter in the organic wastewater includes at least one of phenol, aniline and tetracycline, with a concentration of 50-600 mg / L.

[0042] Furthermore, it also includes adding Na2SO4 electrolyte before degradation, so that the concentration of Na2SO4 electrolyte in the degradation system is 0.15 mol / L.

[0043] Furthermore, the method further includes maintaining stirring at a rotation speed of 350-400 rpm during the degradation process and adjusting the pH value of the degradation system during the degradation process to be neutral.

[0044] Furthermore, the wavelength of the ultraviolet light is 365nm, which is provided by a 400W ultraviolet lamp.

[0045] Furthermore, the degradation time is 1.5h-2h.

[0046] The present invention discloses the following technical effects:

[0047] The BDD-ZnO composite material prepared by the present invention is less restricted and interfered by environmental conditions when used for degrading organic wastewater, can degrade organic pollutants indiscriminately, has the characteristics of cleanliness and high efficiency, and has excellent stability and degradation efficiency.

[0048] BDD has a wide electrochemical window, high current efficiency and long service life. ZnO, as a semiconductor material, can generate electron-hole pairs under light, and then generate free radicals with strong oxidizing ability, effectively degrading organic pollutants. The BDD-ZnO composite material prepared by the present invention combines the high electrocatalytic efficiency of BDD and the strong photocatalytic activity of ZnO, while improving the hydrophilicity of the boron-doped diamond film, showing high efficiency in degrading organic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0050] Figure 1 are the contact angles of BDD and the BDD-ZnO composite materials in Examples 1-3, wherein (a) is Example 1, (b) is Example 2, (c) is BDD, and (d) is Example 3.

[0051] Figure 2 These are SEM images of BDD and BDD-ZnO composite materials prepared in Example 1, wherein (a) is the SEM image of BDD, and (b)-(d) are SEM images of the BDD-ZnO composite materials at different magnifications.

[0052] Figure 3 The SEM images of the cross section of the BDD-ZnO composite material prepared in Example 1 at different magnifications, wherein (a) is magnified 50 times, and (b) is magnified 20 times. DETAILED DESCRIPTION

[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0054] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0058] The raw materials and reagents used in the specific embodiments of the present invention are all commercially available products.

[0059] Unless otherwise specified, the room temperature and normal temperature referred to in the specific embodiments of the present invention are both 20-30°C.

[0060] The processing steps of the single crystal silicon substrate used in the specific embodiment of the present invention include: ultrasonically cleaning the silicon wafer in anhydrous ethanol, acetone and ultrapure water for 5-10 minutes respectively, and after cleaning, placing it in a diamond micropowder suspension with a particle size between 0-0.5μm for ultrasonic 1-2h, then ultrasonically cleaning it with anhydrous ethanol and ultrapure water for 10-15min respectively, and after cleaning, blowing it dry with nitrogen to obtain a single crystal silicon substrate for use.

[0061] Example 1

[0062] The preparation steps of BDD-ZnO composite material include:

[0063] S1, using methane, hydrogen and a boron source (diborane) as precursor gases, and preparing BDD on the above-mentioned single crystal silicon substrate by MPCVD method;

[0064] The process parameters of the MPCVD method are: substrate temperature 850°C, deposition gas pressure 130-150 mbar, microwave power 1.5 kW, hydrogen flow rate 1200 sccm, methane flow rate 40 sccm, boron source flow rate 20 sccm, reaction time 6 h;

[0065] S2, add 1.47 mmol of zinc chloride and 9.43 mmol of anhydrous sodium carbonate powder into 40 mL of deionized water, stir, move the solution and BDD into a hydrothermal reactor, react at 140°C for 12 h, and then collect the reaction product by centrifugation;

[0066] S3. The reaction product was washed with deionized water and anhydrous ethanol, then dried in a vacuum drying oven at 60° C. for 12 h, and then sintered in a tube furnace at 500° C. for 1 h to obtain a BDD-ZnO composite material.

[0067] Example 2

[0068] The preparation steps of BDD-ZnO composite material include:

[0069] S1. Preparation of BDD: same as in Example 1;

[0070] S2, add 2.47mmol of zinc chloride and 9.43mmol of anhydrous sodium carbonate powder into 40mL of deionized water, stir, move the solution and BDD into a hydrothermal reactor, react at 140°C for 12h, and then collect the reaction product by centrifugation;

[0071] S3. The reaction product was washed with deionized water and anhydrous ethanol, then dried in a vacuum drying oven at 60° C. for 12 h, and then sintered in a tube furnace at 500° C. for 1 h to obtain a BDD-ZnO composite material.

[0072] Example 3

[0073] The preparation steps of BDD-ZnO composite material include:

[0074] S1. Preparation of BDD: same as in Example 1;

[0075] S2, add 3.47 mmol of zinc chloride and 9.43 mmol of anhydrous sodium carbonate powder into 40 mL of deionized water, stir, move the solution and BDD into a hydrothermal reactor, react at 140°C for 12 h, and then collect the reaction product by centrifugation;

[0076] S3. The reaction product was washed with deionized water and anhydrous ethanol, then dried in a vacuum drying oven at 60° C. for 12 h, and then sintered in a tube furnace at 500° C. for 1 h to obtain a BDD-ZnO composite material.

[0077] Test example

[0078] The hydrophilic and hydrophobic properties of BDD and the BDD-ZnO composite materials in Examples 1-3 were tested using a contact angle meter. The results are shown in Table 1.

[0079] Table 1

[0080] BDD Example 1 Example 2 Example 3 Contact angle / ° 51.2 10.3 12.5 15.6

[0081] Figure 1 are the contact angles of BDD and the BDD-ZnO composite materials in Examples 1-3, wherein (a) is Example 1, (b) is Example 2, (c) is BDD, and (d) is Example 3.

[0082] From Table 1 and Figure 1 It can be seen that the boron-doped diamond film and the zinc oxide nanorod array grown on the boron-doped diamond film form a heterostructure, which significantly improves the hydrophilicity of the boron-doped diamond film.

[0083] Figure 2 These are SEM images of BDD and BDD-ZnO composite materials prepared in Example 1, wherein (a) is the SEM image of BDD, and (b)-(d) are SEM images of the BDD-ZnO composite materials at different magnifications.

[0084] Figure 3 These are SEM images of the cross section of the BDD-ZnO composite material prepared in Example 1 at different magnifications, where (a) is magnified 50 times and (b) is magnified 20 times.

[0085] Depend on Figure 2-Figure 3 It can be seen that zinc oxide is successfully composited on the surface of the BDD electrode.

[0086] The BDD-ZnO composite material prepared in Example 1 was used as an anode to degrade organic wastewater from the pharmaceutical industry, wherein the concentration of tetracycline in the organic wastewater from the pharmaceutical industry was 50 mg / L, and the concentration of Na2SO4 electrolyte was 0.15 mol / L. The BDD / ZnO composite material was used as an anode, and a platinum sheet was used as a cathode to connect an electrode clip, the electrode distance was maintained at 1 cm, the speed of the magnetic stirrer was controlled to 350 rpm, and a DC regulated power supply (current density was 0.8 A) and a 400 W, 365 nm ultraviolet light source were turned on at the same time, and the degradation was carried out for 1.5 hours. During the degradation process, the pH of the organic wastewater solution was adjusted to about 7, and a sample was taken every 10 minutes. After sampling, it was analyzed and detected using an ultraviolet spectrophotometer, and the degradation efficiency was calculated based on the absorbance. Finally, tetracycline was completely degraded, and the degradation efficiency was 98.81%.

[0087] The BDD-ZnO composite material prepared in Example 1 was used as an anode to degrade agricultural organic wastewater, wherein the concentration of aniline in the agricultural organic wastewater was 100 mg / L, and the concentration of Na2SO4 electrolyte was 0.15 mol / L. The BDD / ZnO composite material was used as an anode, and a platinum sheet was used as a cathode to connect an electrode clip, the electrode distance was maintained at 1 cm, the speed of the magnetic stirrer was controlled to 350 rpm, and a DC regulated power supply (current density was 0.8 A) and a 400 W, 365 nm ultraviolet light source were turned on at the same time, and the degradation was carried out for 2 hours. During the degradation process, the pH of the organic wastewater solution was adjusted to about 7, and samples were taken every 10 minutes. After sampling, the samples were analyzed and detected using an ultraviolet spectrophotometer, and the degradation efficiency was calculated according to the absorbance. Finally, the aniline was completely degraded, and the degradation efficiency was 98.54%.

[0088] The BDD-ZnO composite material prepared in Example 1 was used as an anode to degrade organic wastewater from the chemical industry, wherein the concentration of phenol in the organic wastewater from the chemical industry was 600 mg / L, and the concentration of the Na2SO4 electrolyte was 0.15 mol / L. The BDD / ZnO composite material was used as an anode, and a platinum sheet was used as a cathode to connect an electrode clip, the electrode distance was maintained at 1 cm, the speed of the magnetic stirrer was controlled to 350 rpm, and a DC regulated power supply (current density was 0.8 A) and a 400 W, 365 nm ultraviolet light source were turned on at the same time, and the degradation was carried out for 1 hour. During the degradation process, the pH of the organic wastewater solution was adjusted to about 7, and a sample was taken every 10 minutes. After sampling, the sample was analyzed and detected using an ultraviolet spectrophotometer, and the degradation efficiency was calculated according to the absorbance. Finally, aniline was completely degraded, and the degradation efficiency was 97.29%.

[0089] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0090] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A BDD-ZnO composite material, characterized in that: The BDD-ZnO composite material consists of a boron-doped diamond film and a zinc oxide nanorod array grown on the boron-doped diamond film, wherein the boron-doped diamond film and the zinc oxide nanorod array are in a heterogeneous structure.

2. A method for preparing the BDD-ZnO composite material according to claim 1, characterized in that the steps include: The boron-doped diamond film is immersed in a precursor solution, subjected to hydrothermal reaction, washed, dried, and sintered to obtain the BDD-ZnO composite material; The precursor solution is a mixed aqueous solution of zinc chloride and sodium carbonate.

3. The preparation method according to claim 2, characterized in that: The boron-doped diamond film is prepared on a single crystal silicon substrate by using an MPCVD method with methane, hydrogen and a boron source as precursor gases, wherein the boron source is diborane.

4. The preparation method according to claim 3, characterized in that: The process parameters for preparing the boron-doped diamond film by MPCVD method are: substrate temperature 850-900°C, deposition pressure 130-150mbar, microwave power 1.5-2.0kW, hydrogen flow rate 1200-1300sccm, methane flow rate 40-50sccm, boron source flow rate 20-30sccm, and reaction time 6-8h.

5. The preparation method according to claim 2, characterized in that: The ratio of zinc chloride, sodium carbonate and water in the precursor solution is 1.47-3.47 mmol:9.43 mmol:40-50 mL; and / or, The amount ratio of the boron-doped diamond film to the precursor solution is 0.1-0.3 g: 40-50 mL; and / or, The hydrothermal reaction temperature is 130-150°C and the time is 12h; and / or, The washing is performed using deionized water and ethanol; and / or, The drying temperature is 50-70°C and the drying time is 12 hours; and / or, The sintering temperature is 500-600° C. and the sintering time is 1 hour.

6. Use of the BDD-ZnO composite material according to claim 1 as an electrode material in the degradation of organic wastewater.

7. A method for regulating the hydrophilicity and hydrophobicity of a boron-doped diamond film surface, characterized in that the steps include: Using a mixed aqueous solution of zinc chloride and sodium carbonate as a precursor solution, a ZnO nanorod array is generated on the surface of a boron-doped diamond film through hydrothermal reaction, washing, drying, and sintering to form a BDD-ZnO heterostructure, thereby completing the hydrophilicity and hydrophobicity regulation of the surface of the boron-doped diamond film and obtaining a BDD-ZnO composite material.

8. A method for improving the organic wastewater degradation performance of boron-doped diamond film, characterized in that the steps include: By forming a BDD-ZnO heterostructure on the surface of the boron-doped diamond film, the organic wastewater degradation performance of the boron-doped diamond film is improved; The forming of the BDD-ZnO heterostructure on the surface of the boron-doped diamond film comprises: using a mixed aqueous solution of zinc chloride and sodium carbonate as a precursor solution, generating a ZnO nanorod array on the surface of the boron-doped diamond film through hydrothermal reaction, washing, drying and sintering to form the BDD-ZnO heterostructure.

9. The method according to claim 8, characterized in that The ratio of zinc chloride, sodium carbonate and water in the mixed aqueous solution of zinc chloride and sodium carbonate is 1.47-3.47 mmol:9.43 mmol:40-50 mL; and / or, The amount ratio of the boron-doped diamond film to the precursor solution is 0.1-0.3 g: 40-50 mL; and / or, The hydrothermal reaction temperature is 130-150°C and the time is 12h; and / or, The washing is performed using deionized water and ethanol; and / or, The drying temperature is 50-70°C and the drying time is 12 hours; and / or, The sintering temperature is 500-600° C. and the sintering time is 1 hour.

10. A method for degrading organic wastewater, characterized in that the steps include: Using the BDD-ZnO composite material described in claim 1 as an anode and a platinum sheet electrode as a cathode, connecting electrode clips, adjusting the current density to 0.8-1.0A, and degrading organic wastewater under ultraviolet conditions; The wavelength of the ultraviolet light is 365nm; The organic matter in the organic wastewater includes at least one of phenol, aniline and tetracycline, with a concentration of 50-600 mg / L.

Citation Information

Patent Citations

  • n-shaped zinc oxide nano rod / p-shaped diamond heterojunction photoelectric device and preparation method

    CN101789463A

  • Photo-catalytic material of boron-doped zinc oxide nano rod / p-type diamond heterojunction and preparation method thereof

    CN102513084A

  • N-type ZnO nanorod / p-type diamond ultraviolet photovoltaic detector and preparation method thereof

    CN105870242A

  • Zinc oxide-based composite photo-catalyst with excellent photo-catalytic performance under visible light irradiation

    CN110538649A

  • Boron-doped diamond and method for treating water pollution

    CN119020760A